Information Needs for Bioscience Research - Sengupta, I. N. (Journal of Information and Knowledge, 1978)
Highlights the growth in research output in Biosciences and correlates its impact on bioscientists who need to keep upto date with the wavefront of biosciences research in India and points out its richness and lacunae. Suggests areas for collaboration between India and USA.